An analysis of Parsonian nuclearity from an investigation about the relationship between family structure and parental satisfaction - Luengo R., Tomasa (2008)
The study analyses of the “degree of association” between the satisfaction expressed by the parental figures and the family structure they belong to: Family nuclear, single-parent, binuclear and complex families. In the transversal investigation, 631 mothers and fathers from the middle and upper-middle socio-cultural class took part. The identification of the family structures was undertaken by means of a Family Structure Questionnaire, an adaptation of the Single-parent Family Questionnaire (Rodríguez and Luengo, 2000) and the evaluation of family satisfaction with the AFSE (Barraca and López, 1999). The study shows and that the non-traditional family models are less problematic than that explained by Parsonian structural functionalism.